PERLINDUNGAN HUKUM TERHADAP KONSUMEN MUSLIM DARI PRODUK PANGAN YANG TIDAK BERLABEL HALAL DALAM PERSPEKTIF HUKUM POSITIF YANG TERKAIT DI INDONESIA DAN DI KOREA - ARI MARIYANA ANGRIYANI (Faculty of Law, Maranatha Christian University, 2020)
Halal label is a written form of halal statement to show that the product in question is halal status and functions as consumer protection so that the right of Muslim consumers to consume halal products is guaranteed. Indonesia, as a country with a majority Muslim population, is maintaining the halal value of a product, especially food. Lately, the number of products that have not been certified halal has made it difficult for Muslim consumers to distinguish between halal and non-halal products for consumption. The emergence of various foreign food products from various countries has become commonplace for the community. However, in reality the products circulating in Indonesia are not guaranteed halal, so it needs supervision so that products that are not halal, cannot be circulated and consumed by Indonesian Muslim communities. The purpose of writing this journal is to explain the legal protection efforts for Muslim consumers of food products that are not halal labeled in a positive legal perspective in Indonesia and in Korea. The method used refers to the laws and regulations. The data obtained were analyzed in a qualitative way. Based on research results, regulations relating to Halal products are still very minimal. Therefore, in the Korean trade arrangement it is stated that: